Reductive Power Generated by Mycobacterium leprae Through Cholesterol Oxidation Contributes to Lipid and ATP Synthesis - Rosa, Thabatta L. S. A.; Marques, Maria Angela M.; DeBoard, Zachary; Hutchins, Kelly; Silva, Carlos Adriano A.; Montague, Christine R.; Yuan, Tianao; Amaral, Julio J.; Atella, Georgia C.; Rosa, Patrícia S.; Mattos, Katherine A.; VanderVen, Brian C.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Upon infection, Mycobacterium leprae, an obligate intracellular bacillus, induces accumulation of cholesterol-enriched lipid droplets (LDs) in Schwann cells (SCs). LDs are promptly recruited to M. leprae-containing phagosomes, and inhibition of this process decreases bacterial survival, suggesting that LD recruitment constitutes a mechanism by which host-derived lipids are delivered to intracellular M. leprae. We previously demonstrated that M. leprae has preserved only the capacity to oxidize cholesterol to cholestenone, the first step of the normal cholesterol catabolic pathway. In this study we investigated the biochemical relevance of cholesterol oxidation on bacterial pathogenesis in SCs. Firstly, we showed that M. leprae increases the uptake of LDL-cholesterol by infected SCs. Moreover, fluorescence microscopy analysis revealed a close association between M. leprae and the internalized LDL-cholesterol within the host cell. By using Mycobacterium smegmatis mutant strains complemented with M. leprae genes, we demonstrated that ml1942 coding for 3β-hydroxysteroid dehydrogenase (3β-HSD), but not ml0389 originally annotated as cholesterol oxidase (ChoD), was responsible for the cholesterol oxidation activity detected in M. leprae. The 3β-HSD activity generates the electron donors NADH and NADPH that, respectively, fuel the M. leprae respiratory chain and provide reductive power for the biosynthesis of the dominant bacterial cell wall lipids phthiocerol dimycocerosate (PDIM) and phenolic glycolipid (PGL)-I. Inhibition of M. leprae 3β-HSD activity with the 17β-[N-(2,5-di-t-butylphenyl)carbamoyl]-6-azaandrost-4-en-3one (compound 1), decreased bacterial intracellular survival in SCs. In conclusion, our findings confirm the accumulation of cholesterol in infected SCs and its potential delivery to the intracellular bacterium. Furthermore, we provide strong evidence that cholesterol oxidation is an essential catabolic pathway for M. leprae pathogenicity and point to 3β-HSD as a prime drug target that may be used in combination with current multidrug regimens to shorten leprosy treatment and ameliorate nerve damage.